(3age GdeHGOF ,Md GdeTcdGJ GdJfXjejIs - (3fhQ GdOjf HTjQ(B, (3JGhQjQjJs ((3GQHO(B:s (3YGde GdcJH GdMOjK(B,s, 2009)
(3JWhQ GdacQ GdJfXjej h OQGSI GdefXeI , GdJYQja HGdGTcGdjI , GdJbjje GdJfXjej , GdaYGdjI GdJfXjejI , GdGWGQ GdELQGFj (B.s
(3eQGL U(B.245s
Keywords: (3GdEOGQIs; (3GdJNWjWs; (3JfXje hEOGQIs